Effects of an interdisciplinary intervention on insulin resistance indicators in overweight and obese adolescents - Tornquist, Debora (2020)
Introduction: Overweight children and adolescents are more susceptible to metabolic disorders. However, changes in lifestyle can prevent or delay the appearance of risk factors, highlighting the importance of intervening early in this population. Objective: To analyze the effects of a six months interdisciplinary intervention program on the indicators of insulin resistance and uric acid levels in overweight and obese students. Methods: This is an interventional study in overweight adolescents, composed of a control group (n=19) and an intervention group (n=20). The group participated in a six-month program with nutritional, psychological and physical exercise intervention, three times a week. The values of waist circumference, glucose, insulin, uric acid assessment and HOMA-IR index, were evaluated before and after the program. Results: After 6 months, the intervention group had a significant reduction in waist circumference (p=0.007), HOMA-IR index (p=0.048) and uric acid (p=0.036); the control group did not present differences in the pre and post evaluation. Conclusion: The intervention program was effective in reducing waist circumference, HOMA-IR and uric acid levels in overweight adolescents.